1983
DOI: 10.1093/nar/11.16.5451
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin assembled in the presence of cytosine arabinoside has a short nucleosome repeat

Abstract: Incubation of MSB cells with cytosine arabinoside (1-beta-D-arabinofuranosylcytosine, ara-C) inhibits 3H-thymidine incorporation into nascent DNA while nucleosome core histone synthesis proceeds in molar stoichiometry at about 20% of control rates. The excess nascent histone is incorporated into chromatin and nucleosome cores are assembled normally on the small amount of DNA which is synthesized at submaximal levels of ara-C. This DNA becomes packaged into a shortened nucleosome repeat, however. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…This indicates that the specific cell states or lineage may still require mitosis and therefore that possible stable chromatin structures may yet be important even for myoblast differentiation. Finally, ara-C and other inhibitors of DNA synthesis have differential effects on specific DNA replication origins, such as the DHFR replicon, which is relatively insensitive to inhibition and may still be reassembled into new chromatin in the presence of inhibitors (46,209,210). Altered chromatin assembly during inhibition of DNA synthesis has been reported (209,211).…”
Section: Results Which Appear To Refute Replication-based Differentiamentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the specific cell states or lineage may still require mitosis and therefore that possible stable chromatin structures may yet be important even for myoblast differentiation. Finally, ara-C and other inhibitors of DNA synthesis have differential effects on specific DNA replication origins, such as the DHFR replicon, which is relatively insensitive to inhibition and may still be reassembled into new chromatin in the presence of inhibitors (46,209,210). Altered chromatin assembly during inhibition of DNA synthesis has been reported (209,211).…”
Section: Results Which Appear To Refute Replication-based Differentiamentioning
confidence: 99%
“…Second, terminal replication, like endoreduplication, may be insensitive to (and possibly induced by) the usual inhibitors of DNA replication and may involve a DNA polymerase other than polymerase alpha. Even if these drugs inhibit completion of terminal replication, they do not appear to prevent the initiation of DNA replication, since some origins of replication can be labeled in their presence (121) and can allow the reassembly of new histones onto cis-acting regulatory regions of DNA (121,209,211). Also, because terminal replication is proposed to be the first committed event of terminal differentiation, it could be missed if not specifically sought.…”
Section: Inapparent Terminal Replication In Vertebratesmentioning
confidence: 99%
“…It has been observed that reduction in the replication rate can reduce nucleosome spacing (29). Therefore, more slowly replicating regions of the genome might accumulate a higher density of nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were obtained over a range of hydroxyurea doses from 3 to 20 mM. Incorporation was ended by lysis of the cells in 0.5% sodium dodecyl sulfate (SDS), digestion with proteinase K, and quantitation of 10% trichloroacetic acid precipitable radioactivity (Leffak, 1983a).…”
Section: Methodsmentioning
confidence: 87%